2011
DOI: 10.1007/s11205-011-9806-9
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Trade Openness: The Case of Developing Economies

Abstract: This paper examines the importance of trade openness for attracting Foreign Direct Investment (FDI) inflows, using a sample of 36 developing economies for the period 1990-2008. It provides a direct test of causality between FDI inflows, trade openness and other key variables in developing regions of the world: Latin America, Asia, Africa, CIS (Commonwealth of Independent States) and Eastern Europe. Trade openness is measured by using eight different indicators. The main empirical findings of the panel regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
91
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(113 citation statements)
references
References 20 publications
20
91
0
2
Order By: Relevance
“…The coefficient is positive and significant (P<0.05), providing support for hypothesis 1. This is also consistent with previous research that suggest a positive relationship between trade openness and FDI inflows (Blonigen & Piger, 2014;Liargovas & Skandalis, 2012;Shirazi et al, 2010).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The coefficient is positive and significant (P<0.05), providing support for hypothesis 1. This is also consistent with previous research that suggest a positive relationship between trade openness and FDI inflows (Blonigen & Piger, 2014;Liargovas & Skandalis, 2012;Shirazi et al, 2010).…”
Section: Resultssupporting
confidence: 93%
“…We also include human-capital related factors as suggested by Globerman and Shapiro (2003) to test whether the human capital capabilities (such as education and well-being) play a role in FDI inflows across and between countries. (Liargovas & Skandalis, 2012) argue that trade openness plays a positive and significant role in attracting FDI inflows. The authors studied this relationship in the context of developing countries, selecting only those countries that are considered developed under the categorization of the united nation.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Consistent with Liargovas and Skandalis (2012) [60], our study empirically revealed a positive and significant relationship between market size (GDP as a proxy) and FDI. This result is clearly justified by an assertion that investors have an intention of accruing maximum returns on their investments.…”
Section: Discussion Of the Empirical Resultssupporting
confidence: 90%
“…Çevis & Çamurdan (2007) [8] [30] found GDP (measuring market size) as having a positive impact on FDI flows using panel data with an elasticity of 0.92 and 1.2 using cross-sectional data. Liargovas and Skandalis (2012) [60] …”
Section: Literature Reviewmentioning
confidence: 99%
“…Contrary to the majority of research findings, Asiedu (2002) argued that trade openness' impact on FDI relies on the type of investment and, more specifically, market seeking investments have a positive relationship with lower levels of trade openness, as they are linked to trade restrictions. The reason behind this is the "tariff jumping" hypothesis, stating that foreign companies seeking to enter local markets while findings difficulties in importing their goods, may decide to establish subsidiaries in the host country (Liargovas and Skandalis, 2012). Hypothesis 6a: Inward FDI are positively affected by the level of openness of the host market.…”
Section: Trade Opennessmentioning
confidence: 99%